La Cucaña Destripada - Ramos, M. (Libro de Actas del 1º Congreso Internacional de Patios de Cordoba, 2020)
Using as an example the very recent turistification process of the city of Lisbon, this essay seeks to understand how the instrumentalization of urban patrimonialised spaces, and their convergent gentrification, opens the way to new ritual practices of the so-called cultural tourism. Through the neoliberal turn, in the period of globalization, that drives the widespread commodification of leisure, we are now all potential citizens of the Cocagne – taken here as the epitome of the popular imaginary of leisure.